2014
DOI: 10.2149/tmh.2014-09
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cytokines with Severe Dengue in Children

Abstract: Background: Dengue virus infection is a major public health problem. A hypothesis put forward for severe dengue is the cytokine storm, a sudden increase in cytokines that induces vascular permeability. Previous studies and our recent meta-analysis showed that IL-6, IL-8, IFNγ, TNFα, VEGF-A and VCAM-1 are associated with dengue shock syndrome. Therefore, in this study we aim to validate the association of these cytokines with severe dengue. Methods & Findings: In a hospital based-case control study in Vietnam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 42 publications
(50 reference statements)
4
30
1
Order By: Relevance
“…As opposed to previous study, VCAM-1 could not differentiate among the different severity of dengue cases in our study [34]. Other studies were conducted in children indicated VCAM-1 could differentiate the different severity of dengue cases [17,35,36].…”
Section: Discussioncontrasting
confidence: 99%
“…As opposed to previous study, VCAM-1 could not differentiate among the different severity of dengue cases in our study [34]. Other studies were conducted in children indicated VCAM-1 could differentiate the different severity of dengue cases [17,35,36].…”
Section: Discussioncontrasting
confidence: 99%
“…Our data showed that IL-6 expression level in DHF patients was significantly higher than that in DF patients and healthy controls, which is completely in agreement with the findings of other report [20]. A number of clinical studies demonstrated higher level of pro-inflammatory cytokines most importantly IL-6 in sera from either DF or DHF patients in comparison with healthy subjects [21][22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…1 TNF-α is a key pro-inflammatory cytokine that has been associated with many biological functions such as lipid metabolism 11 ; it is well known that DF and DHF patients have significantly higher levels of pro-inflammatory cytokines. 12,13 In the present study, we found increased levels of cholesterol and LDL in HBD compared with dengue patients, whereas cholesterol, LDL, and HDL levels were significantly lower in DHF than in DF and/or HBD. Furthermore, we found higher levels of TNF-α in DF patients compared to HBD.…”
supporting
confidence: 50%
“…Lipid metabolism is extensively regulated by cytokines during the host response to infection . TNF‐α is a key pro‐inflammatory cytokine that has been associated with many biological functions such as lipid metabolism; it is well known that DF and DHF patients have significantly higher levels of pro‐inflammatory cytokines …”
Section: Discussionmentioning
confidence: 99%